2013
DOI: 10.5902/2236117010747
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação E Correlação De Parâmetros Fisiológicos E Índices Bioclimáticos De Vacas Holandês Em Diferentes Estações

Abstract: ResumoObjetivou-se com este trabalho determinar os parâmetros fisiológicos de vacas da raça Holandês em lactação durante a estação de inverno e de primavera e correlacionar tais parâmetros com os índices bioclimáticos. Foram utilizadas nove vacas da raça Holandês em um delineamento inteiramente ao acaso, em arranjo de parcelas subdivididas com medidas repetidas no tempo. Os dados foram coletados durante o inverno e a primavera, nos quais foram medidas a frequência respiratória (FR), a frequência cardíaca (FC),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
3
1
2
Order By: Relevance
“…The positive correlation of GHTI with RT, BST, and RR found in the research matches the results reported by Silva et al (2011a), who found highly significant correlations of GHTI with RT, BST, RR, and HR both in the rainier and the less rainy seasons in Belém, PA, Brazil. In the semi-arid Agreste region of the Brazilian state of Pernambuco, in an experiment with buffalo heifers, Costa (2007) found a positive Avila et al (2013), if AT is higher than the critical limit, the skin also warms up and this heat sensation is conducted to the hypothalamus, which is responsible for activating surface blood vessel dilation to lead to a greater blood flow along the body surface to dissipate heat. This phenomenon causes thermal exchange to the skin by conduction and, next, to the environment by radiation, which increases BST values.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The positive correlation of GHTI with RT, BST, and RR found in the research matches the results reported by Silva et al (2011a), who found highly significant correlations of GHTI with RT, BST, RR, and HR both in the rainier and the less rainy seasons in Belém, PA, Brazil. In the semi-arid Agreste region of the Brazilian state of Pernambuco, in an experiment with buffalo heifers, Costa (2007) found a positive Avila et al (2013), if AT is higher than the critical limit, the skin also warms up and this heat sensation is conducted to the hypothalamus, which is responsible for activating surface blood vessel dilation to lead to a greater blood flow along the body surface to dissipate heat. This phenomenon causes thermal exchange to the skin by conduction and, next, to the environment by radiation, which increases BST values.…”
Section: Discussionmentioning
confidence: 96%
“…The new indices were also strongly positively correlated with RR, which suggests that the higher the index values, the higher the RR values are in order to increase heat loss by evaporation since the inhaled air dissipates heat from the organism when heated while traveling through the respiratory system (Avila et al 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Não houve diferença significativa (P>0,05) na TSC, demonstrando que a vasodilatação periférica realizada pelos animais como forma de perda de calor para o ambiente foi semelhante durante os meses estudados (Tabela 3). Os valores absolutos obtidos para TSC neste estudo foram superiores aos observados por Ávila et al (23) , que avaliaram o efeito do clima no município de Palmeira das Missões -RS sobre os parâmetros fisiológicos de vacas holandesas em lactação. A ausência de estrutura na propriedade avaliada, aliada à não disponibilidade de árvores ou proteção dos animais contra a radiação solar, contribuíram para a maior TSC observado nos animais.…”
Section: Resultado E Discussãounclassified
“…Visto que, os animais necessitam de um ambiente com condições que favoreçam o metabolismo e homeostase do animal. Desse modo, as condições de instalação devem ser modificadas conforme o tipo de criação, o manejo adotado e clima do local (Abreu et al, 2011;Avila et al, 2013;Polli et al, 2020) No julgamento do conforto ou desconforto dos animais pelos elementos climáticos comumente são utilizados índices, que unificam os seus efeitos e que possuem relação com indicadores fisiológicos e comportamentais dos animais (Neves et al, 2009;Avila et al, 2013;Marins et al, 2020). São bons exemplos de indicadores, o índice de temperatura do globo negro e umidade (ITGU), índice de temperatura e umidade (ITU), e carga térmica radiante (CTR) que vem sendo bastante utilizados.…”
Section: Introductionunclassified